Formulation and Evaluation of Nicotine Polacrilex Chewable Tablets by Direct Compression - Shashank Namannavar; Sneha R Jakaraddi; Dr. Chandrashekar C. Patil; Arjun L Uppar (Asian Journal of Pharmaceutical Research and Development, 2026)
Nicotine polacrilex chewable tablets were developed as an effective dosage form for nicotine replacement therapy to help reduce smoking dependence. The present study focused on the formulation and evaluation of chewable tablets using suitable excipients to improve taste, stability, and drug release. Tablets were prepared by the direct compression method using ingrediaents such as mannitol, microcrystalline cellulose, sodium starch glycolate, and flavouring agents. Pre-compression studies indicated good flow properties of the powder blend, ensuring uniform tablet formation. The prepared tablets were evaluated for various parameters including weight variation, hardness, friability, thickness, disintegration time, and in-vitro drug release. All formulations complied with pharmacopeial limits, showing acceptable mechanical strength and rapid disintegration. Among the formulations, batch NT4 showed the best performance with optimum hardness, lowest friability, and faster disintegration time. In-vitro dissolution studies demonstrated effective drug release within a short period, indicating suitability for rapid nicotine delivery. Overall, the developed chewable tablets offer a convenient, patient-friendly, and effective approach for nicotine replacement therapy.